An Assay to Quantify the Two Plasma Isoforms of Factor V - Hoekema, Lico; Rosing, Jan; Tans, Guido (Thrombosis and Haemostasis, 2000)
Blood coagulation factor V (FV) circulates in the blood in two forms, designated FV1 and FV2. In model systems containing purified proteins FV1 appears to be more thrombogenic than FV2. Recently, we reported that in plasma from carriers of the R2 haplotype, a polymorphism which encodes several amino acid changes in FV and which is associated with an increased risk of thrombosis, the FV1/FV2 ratio is shifted in favor of the more thrombogenic form FV1. Here we describe in detail the assay that enables quantification of the plasma levels of FV1 and FV2. FV present in highly diluted plasma samples was activated with thrombin and the FVa generated was subsequently quantified in two prothrombinase-based assay systems. In the first assay, which is performed at saturating amounts of FXa and phospholipid vesicles with a high mole fraction phosphatidylserine, FVa1 and FVa2 express the same cofactor activity in prothrombin activation. Hence, this assay quantifies the total FV level (FV1 + FV2) present in plasma. In the second assay, which is performed at suboptimal amounts of FXa and phospholipid vesicles with a low mole fraction phosphatidylserine, FVa2 has approximately an 8-fold higher cofactor activity than FVa1. Therefore, the response in this assay depends on the relative amounts of FV1 and FV2 in the plasma sample. Calibration curves made with samples containing known concentrations of purified FVa1 and FVa2 subsequently allowed calculation of the amounts of FV1 and FV2 present in plasma.
Keywords: Blood coagulation; Factor V; thrombosis